Disease trajectory and competing risks of patients with cirrhosis in the US - Mohsen Mohammadi; Bima J. Hasjim; Salva N. Balbale; Praneet Polineni; Alexander A. Huang; Mitchell Paukner; Therese Banea; Oriana Dentici; Dominic J. Vitello; Joy E. Obayemi; Andrés Duarte-Rojo; Satish N. Nadig; et al. (PLoS ONE, 2025)
Background Cirrhosis is a dynamic disease process leading to liver-related death, which has increased by over 65% over the last decade. Unpredictable hepatic decompensation complications are a major source of morbidity and mortality. Thus, accurately characterizing disease progression through discrete stages of cirrhosis is critical towards implementing timely intervention and liver transplant (LT) waitlisting. Methods A retrospective, longitudinal, population-cohort study of adult patients with cirrhosis from a US metropolitan area (2006–2012) was conducted. Clinical diagnoses were defined by ICD-9 and CPT codes. Cirrhosis stages were defined as: compensated without portal hypertension (Stage 1), compensated with portal hypertension (Stage 2), variceal bleeding (Stage 3), hepatic encephalopathy (Stage 4a), ascites (Stage 4b), and ≥2 different decompensating complications (Stage 5). Multivariate Fine-Gray competing risk survival analysis adjusted for clinicodemographic covariates. Results Among 12,196 patients with cirrhosis, the mean (±SD) age was 56.8 (±11.7) years with a follow-up time of 2.35 (±1.81) years. A novel 5-stage disease progression framework was used. The 1-year mortality rates for each stage were 7.3% for Stage 1, 5.4% for Stage 2, 11.4% for Stage 3, 10.0% for Stage 4a, 20.2% for Stage 4b, and 43.8% for Stage 5. Compared to those in Stage 1, Stage 3 (sHR:1.83, 95% CI:1.36–2.48, P<0.001), Stage 4b (sHR:1.45, 95% CI:1.23–1.70, P<0.001), and Stage 5 (sHR:1.95, 95% CI:1.71–2.23, P<0.001) patients had higher risks of mortality. Additional disease progression rates were identified. Conclusion Even among patients with compensated cirrhosis, the 1-year mortality rate was as high as 7.3% and subsequently increases with each decompensation complication. This one-year mortality rate is higher than 5-years mortality rate reported in previously known non-US studies. The highest associated risk of death was observed among patients with ≥2 different decompensating complications (95.2%), variceal bleeding (83.2%) and ascites (44.9%). Overall, patients in advanced stages of cirrhosis were more likely to die than they were to receive a LT, suggesting that patients should be referred and waitlisted for LT earlier in the disease process.